Fear towards insects and other arthropods: a cross sectional study in a Malaysian university - Aishah Hani Azil; Mohd Adnan Yakub; Norhaty Hassan; Shalisah Sharip (Penerbit Universiti Kebangsaan Malaysia, 2021)
Insects and other arthropods can elicit fear and disgust in certain individuals and communities which is yet to be explored in Malaysia. Therefore, we aimed to determine the prevalence of fear and disgust toward varied arthropods and compare the level of emotions between female and male respondents and the different arthropod types. A cross-sectional survey using a new designed arthropods survey was performed among 224 undergraduate students in Universiti Kebangsaan Malaysia. Based on our study, more than half of the respondents feared scorpion, wasp, centipede, bee, blister beetle and cockroach. Meanwhile, more than half of the respondents reported disgust toward maggot, cockroach, caterpillar, centipede, sago larvae and head lice. Female students who formed the majority of respondents reported higher fear and disgust toward the top-fifteen chosen insects. The most feared arthropod is the scorpion, while maggot (i.e. fly larvae) is the most disgusted arthropod. Statistically significant differences of fear were found between female and male respondents toward most arthropods, whereas no significant differences were found between genders for disgust toward most arthropods. In addition, previous history of spider bite is significantly associated with fear of spiders. This study revealed fear of arthropods is prevalent among university students in Malaysia. Persistent fear toward arthropods can lead to entomophobia, a specific phobia that may require intervention by health professionals.